CD36 plays a critical role in proliferation, migration and tamoxifen-inhibited growth of ER-positive breast cancer cells. (December 2018) - Liang, Yu; Han, Hao; Liu, Lipei; Duan, Yajun; Yang, Xiaoxiao; Ma, Chuanrui; Zhu, Yan; Han, Jihong; Li, Xiaoju; Chen, Yuanli
Abstract Tamoxifen inhibits estrogen receptor (ER)-positive breast cancer growth while CD36 potentiates cancer metastasis. The effects of CD36 on proliferation/migration of breast cancer cells and tamoxifen-inhibited ER-positive cell growth are unknown. In this study, we correlated the mortality of breast cancer patients to tumor CD36 expression levels. We also found CD36 was higher in ER-rich (MCF-7>T-47D~ZR-75-30) than ER-negative (MDA-MB-231) cells. CD36 siRNA decreased viability and migration of MCF-7 and MDA-MB-231 cells with more potent effects on MCF-7 cells. Inversely, high expressing CD36 enhanced cell growth/migration. Mechanistically, CD36 increased expression of genes responsible for cell proliferation, migration and anti-apoptosis. CD36 also activated ERα and ER-targeted genes for cell cycles, and phosphorylated ERK1/2 (p-ERK1/2). Tamoxifen inhibited CD36 and p-ERK1/2 in ERα-positive but not ERα-negative cells. Reciprocally, inhibition of MCF-7 cell growth by tamoxifen was attenuated by high expressing CD36. CD36, ERα and p-ERK1/2 expression was higher in tamoxifen-resistant MCF-7 (MCF-7/TAMR) cells than normal MCF-7 cells. However, CD36 siRNA restored the capacity of tamoxifen inhibiting MCF-7/TAMR cell growth. CD36 antibody inhibited cell growth and expression of ERα, p-ERK1/2 and CCND1. Therefore, our study unveils a pro-tumorigenic role of CD36 in breast cancer by enhancing proliferation/migration of breast cancer cells while attenuating tamoxifen-inhibited ER-positive cell growth.